Transformation of the peasant society, articulation and underdevelopment in the Peruvian cotton farms: The Pisco Valley, 1883-1925 - Peloso, Vincent C. (1983)
Two of the most widespread hypotheses that explain how capitalist underdevelopment took shape in Peru in the 20th century are based on class analysis. One of them underlines the condescending role of the ruling class, especially the landed sector, in subjecting the economy to a predominance of export agriculture and mining, thus hindering the transformation of social relations to give way to a proletariat so social relations were transformed to make way for an independent and class-conscious proletariat. The other hypothesis highlights the response of the rural masses to the agro-export policy of the ruling class, and points out that as they were responding to the hegemonic order of the landowners, the haciendas and plantations became critical institutions through which they emerged and later Opportunities for a transformation of rural society were obstructed. These ideas have stimulated research on landowners and peasants, examining the axes around which their relationships moved in the early stages of modernization of rural economies.